438 Perception of physical child abuse in a french emergency department in 2013–2014. (1st September 2016) - Bailhache, Marion; Alioum, Ahmadou; Salmi, Louis-Rachid
Abstract : Background: The perception of abuse might explain why France has not prohibited all forms of corporal punishment; it has potential important implications on uses of corporal punishment, intention to report abuse cases and acceptability of laws or prevention programs. The aim of our study was to compare perception of physical child abuse between professionals and parents in an emergency department and determine which characteristics are associated with this perception. Methods: A cross-sectional study was conducted from November 2013 to October 2014 in the emergency department of the Bordeaux paediatric university hospital, France. An anonymous self-questionnaire, including vignettes describing hypothetic situations of potential physical child abuse and items related to socio-demographic and family characteristics, was administered to professionals and parents. Vignettes included varying child's age, child's behaviour, frequency of caregiver's behaviour, hitting with/without an object, and child's target body part. Respondents were asked to rate the acceptability of situations of eight random vignettes on a 100-mm visual analogic scale. Analyses were multivariate mixed Poisson regressions. Results: One thousand and one participants assessed the vignettes. Participants were predominantly female (64%), married or living with a partner (87%), with a median age of 34 years. Professionals significantly assessed vignettes as more acceptable than parents (mean rating multiplied by 2.8; p < 0.001). Parents who had a child under one-year-old (multiplied by 0.7), those who had consulted many times in the past year (multiplied by 0.7), and those who had less children, were less tolerant. All vignette characteristics were significantly associated with the acceptability. Conclusions: Such differences indicate the need for additional research to better appreciate consequences and severity of physical violence toward children, and the need to educate parents and professionals.